Dutch Commerce and Chinese Merchants in Java: Colonial Relationships in Trade and Finance, 1800-1942 - Alexander Claver (Brill, 2014)
Dutch Commerce and Chinese Merchants in Java describes the vanished commercial world of colonial Java. Alexander Claver shows the challenges of a demanding business environment by highlighting trade and finance mechanisms, and the relationships between the participants involved.
Keywords: 330; Indonesia; Kaufleute; Chinesen; Großmacht; Niederlande; Kolonialismus; Java